Estudo timpanométrico em crianças pré-escolares - Guimarães, Adamastor Tavares da Cunha; Chisté, José; Guimarães, Vanessa C.; Bassanesi, Humberto C. (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento.